Lower Brain-Derived Neurotrophic Factor in Patients with Prader-Willi Syndrome Compared to Obese and Lean Control Subjects - Han, Joan C. (The Endocrine Society, 2010)
Context: Brain-derived neurotrophic factor (BDNF) haploinsufficiency is associated with hyperphagia and obesity in both animals and humans. BDNF appears to function downstream of the leptin-melanocortin signaling pathway to control energy balance. The potential role of BDNF in the etiology of the severe hyperphagia associated with PWS has not been previously explored. Objective: The aim was to compare BDNF concentrations in subjects with PWS and obese controls (OC) and lean controls (LC). Design and Setting: We conducted a cross-sectional study at an outpatient clinical research center. Participants: We studied 13 subjects with PWS [five females and eight males; mean ± sd: age, 11.0 ± 4.1 yr; body mass index (BMI)-Z, 2.05 ± 0.78], 13 OC (eight females, five males; age, 12.3 ± 2.7 yr; BMI-Z, 2.18 ± 0.61), and 13 LC (six females, seven males; age, 12.4 ± 2.6 yr; BMI-Z, −0.57 ± 0.73). Main Outcome Measure: BDNF was measured in serum and plasma by ELISA. Analysis of covariance adjusted for age, sex, and BMI-Z. Results: All groups were comparable for age (P = 0.50) and sex distribution (P = 0.49). BMI-Z was comparable between PWS and OC (P = 0.89) and lower in LC (P < 0.001). Adjusted serum BDNF was comparable (P = 0.35) in OC (mean ± sem: 13.5 ± 1.2 ng/ml) and LC (19.2 ± 1.3 ng/ml), but lower in PWS (8.3 ± 1.2 ng/ml; P = 0.01 vs. OC; P = 0.03 vs. LC). Adjusted plasma BDNF in PWS (217 ± 130 pg/ml) was lower than OC (422 ± 126 pg/ml; P = 0.02), but statistically comparable with LC (540 ± 143 pg/ml; P = 0.10). Conclusions: Lower BDNF in PWS suggests insufficient central BDNF production because BDNF in peripheral circulation is believed to reflect cerebral BDNF output. Decreased BDNF may be a potential cause for the disordered satiety and morbid obesity associated with PWS. Further studies are needed to confirm this preliminary pilot study in a larger cohort of patients with PWS.